Lived experience in human-building interaction (HBI): an initial framework - Economidou, Eléni; Itzlinger, Alina; Frauenberger, Christopher (Frontiers in Computer Science, 2024)
1 The emerging field of human building interaction (HBI) has its roots in the historical trends of the development of architecture and human-computer interaction (HCI). Advancements in Building Information Modelling (BIM), sensing, and actuation technologies as well as the commodification and miniaturisation of microprocessors the past two decades are transforming what once were quixotic visions of a cybernetic architecture into reality. The interfacing ::::This ::::: new : reality which integrates computation with architecture opens up different kinds of engagements in the ways we design, use, and inhabit our built environments. A question that follows this new reality is:how can we conceptualise human experience in such environments? Thus far, the lived human experience of such interactions has been an overlooked aspect in HBI-related research. In this paper we provide an initial experience framework for HBI underpinned by existing literature from the HCI and architecture domains on the subjective, lived-in experience of architecture and findings derived from a case study of a field-deployed HBI interface. The research objective of our framework is to outline aspects of HBI lived experiences that can be used as guiding lenses for HBI designers and practitioners who wish to design for and assess such experiences.